2020
DOI: 10.1103/physrevlett.124.073402
|View full text |Cite
|
Sign up to set email alerts
|

Self-Bound Doubly Dipolar Bose-Einstein Condensates

Abstract: We analyze the physics of self-bound droplets in a doubly dipolar Bose-Einstein condensate (DDBEC) composed by particles with both electric and magnetic dipole moments. Using the particularly relevant case of dysprosium, we show that the anisotropy of the doubly-dipolar interaction potential is highly versatile and nontrivial, depending critically on the relative orientation and strength between the two dipole moments. This opens novel possibilities for exploring intriguing quantum many-body physics. Interesti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 62 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…The choice of J d = 10J s is physically realizable in polar molecules [3] and Dysprosium atoms [19] with µ d /µ 0.1 in units of D/µ B , with µ B Bohr's magneton. Note that with J d = 10J s , the next-nearest neighbour EDM-EDM interactions are of similar magnitude to the nearest neighbour MDM-MDM interactions.…”
Section: Ground State Phase Diagrammentioning
confidence: 99%
“…The choice of J d = 10J s is physically realizable in polar molecules [3] and Dysprosium atoms [19] with µ d /µ 0.1 in units of D/µ B , with µ B Bohr's magneton. Note that with J d = 10J s , the next-nearest neighbour EDM-EDM interactions are of similar magnitude to the nearest neighbour MDM-MDM interactions.…”
Section: Ground State Phase Diagrammentioning
confidence: 99%
“…In experiments with 11 Na, 7 Li, 39 K and 85 Rb BECs, contribution to the dynamics from atomic magnetic moments is usually neglected, as the corresponding dipole-dipole interactions (DDIs) are very weak [63]. On the other hand, BEC has also been created in gases of 52 Cr [64][65][66], 168 Er [67], 164 Dy [68,69] and 162 Dy [70] atoms, which carry large magnetic moments (μ ≥ 6μ B , where μ B is the Bohr magneton).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, DDI may be positive in one direction and negative in another [71]. Dipolar BECs have been investigated in broad contexts, such as the existence of the quantum liquid stabilized by quantum fluctuations, spin-orbit coupling, physics of lattices beyond the standard Bose-Hubbard model, parametric oscillations, roton excitations, modulation instability, anisotropic solitons, vortex scissors oscillations, structure formation, self-bound droplets in a doubly dipolar BEC, and dipolar BEC in a bubble trap [72][73][74][75][76][77][78][79][80][81][82][83][84][85].…”
Section: Introductionmentioning
confidence: 99%
“…The dimension crossovers from 1D → 3D [43] and 2D → 3D in binary BECs have also been analysed [44]. Droplet with constituents having electric and magnetic moments have been explored [45], where it is observed that the droplets experience a crossover from the cigar to pancake shapes in terms of relative dipole orientations. A new type of droplet in binary magnetic gases has been recently found, where single component self-bound droplet can couple with other magnetic components, not in the droplet phase [46].…”
Section: Introductionmentioning
confidence: 99%